Moroccan Arabic’s adaptation of French Nasal Vowels: An OT-theoretic analysis - CHOUIA, MOUHCINE (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
This study investigates the phonological adaptation of French nasal vowels into Moroccan Arabic (MA), focusing on the processes that govern this transformation. In MA, French nasal vowels typically undergo "VNASALUnpacking," a process where the nasal vowel is split into an oral vowel followed by a nasal consonant to avoid onsetless syllables. MA speakers perceive French nasal vowels as VN sequences, a phenomenon supported by cross-linguistic evidence of the biphonemic nature of nasal vowels. Using an Optimality Theory (OT) framework, this adaptation is driven by the UNPACKNASALV constraint, which enforces the decomposition of nasal vowels into two segments. This process is further influenced by the CODA-COND NASAL-Stop constraint, resulting in nasal place assimilation and specific output forms in MA. The markedness constraint UNPACKNASALV dominates the anti-unpacking faithfulness constraint INTEGRITY, leading to adaptations that favor structural conditions in MA, such as avoiding *VNASAL and ensuring syllables have onsets (ONSET), at the expense of lexical contrast. French, on the other hand, unpacks nasal vowels primarily in liaison contexts to avoid vowel hiatus, due to the high-ranking NOHIATUS constraint. This preference for unpacking over deletion indicates that the MAX-IO constraint is ranked higher than UNPACKNASALV in French. Yoruba, however, resolves vowel hiatus through deletion rather than unpacking, showcasing different phonological strategies across languages. In MA, the nasal vowels of borrowed French words are realized as VN sequences, neutralizing the orality-nasality contrast in the input. This process indicates the lower ranking of the faithfulness constraint MAX-IO (V) in MA, especially when unpacking would lead to onsetless syllables. The findings highlight the interplay between markedness and faithfulness constraints in the phonological adaptation of borrowed words, emphasizing the structural priorities of MA.